1999
DOI: 10.1152/jappl.1999.86.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Convertase activity in alveolar surfactant and lamellar bodies in fetal, newborn, and adult rabbits

Abstract: Conversion of heavy-aggregate alveolar surfactant (H) to a light-aggregate, nonsurface active form (L) is believed to involve the activity of an enzyme, namely, convertase. This conversion can be reproduced in vitro by the surface-area cycling technique. The purpose of the present study was to use this technique to investigate the developmental aspects of convertase activity in fetal, newborn, and adult rabbits. H was isolated from alveolar lavage from term [31-day gestation (31d)] fetal rabbit pups, 1-, 4-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…At first glance, this hypothesis seems appealing because it provides a new level of regulation for extracellular surfactant metabolism and plausible because it was known previously that LBs contain cytochemically demonstrable enzymes. Indeed, the convertase could be a product of the type II cells, co-secreted with lipids into the ALF (161,162). However, as Williams pointed out earlier (141), a co-secretion of enzymes with their substrates would necessitate that their activity be blocked within the vesicles and reactivated once the material is released.…”
Section: Convertasementioning
confidence: 99%
“…At first glance, this hypothesis seems appealing because it provides a new level of regulation for extracellular surfactant metabolism and plausible because it was known previously that LBs contain cytochemically demonstrable enzymes. Indeed, the convertase could be a product of the type II cells, co-secreted with lipids into the ALF (161,162). However, as Williams pointed out earlier (141), a co-secretion of enzymes with their substrates would necessitate that their activity be blocked within the vesicles and reactivated once the material is released.…”
Section: Convertasementioning
confidence: 99%
“…This process is thought to involve both SP-B [87] and SP-C (for review, see [71,86]). The final step of conversion, from surface-active surfactant into inactive vesicular forms, appears to depend on an AE2-cell-derived enzyme termed convertase [88,89]. …”
Section: The Ae2 Cell As the Source Of Alveolar Surfactantmentioning
confidence: 99%
“…The natural surfactants were isolated from adult and fetal rabbit lungs using differential and density gradient procedures, which have been described in detail in previous reports (21,22,23). We have previously reported that the surfactant preparation isolated by this procedure consists entirely of characteristic lamellar body (LB)-like structures, as evidenced by electron microscopic analysis (22), and is virtually free from contamination by other nonsurfactant membrane components, as determined by marker enzyme assays (22).…”
Section: Methodsmentioning
confidence: 99%
“…We recently used this model to examine the effects of the intratracheal administration of different surfactant preparations on lung water clearance (16,24) in preterm rabbits ventilated for periods of up to 6 h. A surfactant preparation obtained from term fetal rabbits (FRS) was associated with longer survival and improved lung water clearance compared with an adult rabbit surfactant preparation (ARS) and two commercially available preparations, Exosurf and Survanta. In vitro studies on FRS in our laboratory (23) have shown that, after 3 h of surface area cycling (7), FRS converted from the biologically active heavyaggregate form (H) to the inactive light-aggregate (L) form at a significantly slower rate than ARS (i.e., Ͻ20% vs. ϳ60%). If FRS functions in a similar manner when instilled into lungs, the bioavailability of its active (H) form would be expected to be longer compared with ARS and other surfactants.…”
mentioning
confidence: 99%